Meningkatkan Hasil Belajar Siswa Melalui Metode Make A Macth Tentang Mata Pelajaran PAI di Kelas IV di SDN 9 Kunangan Parik Rantang - Yanti, Nelda (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN 9 Kunangan Parik Rantang in Islamic Religious Education (PAI) by using the Make a Match method. This research employs a Classroom Action Research (CAR) approach, carried out in two cycles. Each cycle consists of planning, action, observation, and reflection. The results of the study indicate that the implementation of this method significantly improves students’ learning outcomes. In Cycle I, there was an improvement in student engagement in learning, and Cycle II showed more optimal results with an increase in test scores and student involvement. The Make a Match method proves to be effective in enhancing motivation, participation, and understanding in PAI lessons.